KARAKTERISTIK PERUSAHAAN, KOMISARIS INDEPENDEN DAN PENGUNGKAPAN SUSTAINABILITY REPORTING - Setiadi, Iwan; Abbas, Dirvi Surya; Hidayat, Imam (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study is to determine the influence of profitability, leverage, company size and independent board of commissioners on the disclosure of sustainability reports. The research design used in this research is a quantitative associative approach. The population in this study is companies in various industrial sectors listed on the Indonesia Stock Exchange for the 2017-2018 period. The sampling technique used in this study was a purposive sampling technique and was obtained from 12 company samples. The data analysis method used in this study is using the multiple linear regression data analysis method. The research data was obtained from the www.idx.co.id website. The results of the partial test show that profitability (ROE), company size and independent commissioners have no effect on the disclosure of the sustainability report. Meanwhile, leverage (DAR) has a positive effect on the disclosure of sustainability reports.